New rising entities in cancer of unknown primary: Is there a real therapeutic benefit?. (March 2020) - Rassy, Elie; Parent, Pauline; Lefort, Felix; Boussios, Stergios; Baciarello, Giulia; Pavlidis, Nicholas
Highlights: CUP accounts for approximately 1–3 % of all malignant neoplasms. CUP patients are categorized according to their clinicopathological characteristics. Empiric CUP regimens may be suboptimal in some patients within the unfavorable subsets. CUP with colorectal, lung and renal - profiles seem to arise as distinct CUP entities. Abstract: Cancers of Unknown Primary Site (CUP) account for approximately 1–3 % of all malignant neoplasms. It represents a heterogeneous group of malignancies without a detectable primary and is characterized by aggressive clinical behavior. Patients with CUP are presumably categorized into prognostic subsets according to their clinical and pathological characteristics. The majority of these patients are chemoresistant and treated with empiric chemotherapy regimens which yield limited survival. Recent diagnostic advances have led to the identification of a higher percentage of culprit primaries among which colorectal, lung and renal tumors. The empiric CUP regimens may be suboptimal in these patients which explain in part their poor prognosis. In the absence of prospective randomized studies to prove the benefit of site-specific therapy in these subsets, we reviewed the literature to assess whether CUP with colorectal, lung and renal - profiles should be treated similarly to the correspondent primary tumors.